Many splendored things: Sexuality, playfulness and play - Paasonen Susanna (United Kingdom, 2022)
This article makes a theoretical argument for the productivity of the notions of playfulness
and play in feminist and queer studies of sexuality. Defined as a mode of sensory
openness and drive towards improvisation, playfulness can be seen as central to a range
of sexual activities from fumbling, random motions to elaborate, rehearsed scenarios.
Play in the realm of sexuality involves experimentations with what bodies can feel and
do. As pleasurable activity practised for its own sake, play involves the exploration of
different bodily capacities, appetites, orientations and connections. Understood in this
vein, play is not the opposite of seriousness or simply synonymous with fun. Driven by
the quest for bodily pleasure, play may just as well be strained, dark and hurtful in the
forms that it takes and the sensory intensities that it engenders. This article argues that
the mode of playfulness and acts of play allow for pushing previously perceived and
imagined horizons of embodied potentiality in terms of sexual routines and identifications
alike. It examines the productive avenues that the notions of playfulness and play
open up in conceptualising the urgency of sexual pleasures, the contingency of desires
and their congealment in categories of identity.
Keywords
Desire, fantasy, play, playfulness, pleasure